EFFECTS OF THE MULTISPORT ACTIVITY PROGRAM ON YOUTH FOOTBALL PLAYERS’ MOTOR SKILL DEVELOPMENT - Herczeg, Gábor; Szántai, Levente; Czebe, Norbert; Simon, Róbert; Kárász, Dávid; Halasi, Szabolcs; Lepes, Josip; Győri, Ferenc (Stadium - Hungarian Journal of Sport Sciences, 2024)
Objective: Our study aimed to compare the dynamic leg strength, acceleration, running speed, agility, and ball-handling skills of young football players. Material and method: Forty-two players members of the Szeged-Csanád Grosics Academy participated in the so-called "Multisport Activity Program" (SG) (nsg=42), whereas the control group (CG) involved players from the academy’s partner clubs (ncg=109). Our testing procedure included: standing long jump, 10 m, and 30 m run, COD 505, and T-Test with ball dribbling. Results: We found that the dynamic leg power of the SG players was significantly improved. The means of the T-tests demonstrated (p<0.001) improved ball dribbling skills in the SG group. We found no significant difference in the COD 505 test results. The results of the standing long jump, 10 m, 30 m, COD 505, and ball control tests are strongly correlated; however, none explain the minor COD difference. Conclusion: It is beneficial for players to participate in multisport sessions involving various agility and ball control tasks. The COD 505 test results demonstrated smaller differences between dominant and non-dominant sides in SG participants. We suggest they are less likely to develop unilateral movement patterns that lead to overtraining injuries. The results indicate that implementing a "Multisport activity program" benefits youth athlete.